A study on the learning spaces of UP students and its implications to the General Reference Section of the UP Diliman Main Library - Orijuela, Sherwin R.; Apolinario, Rhea Rowena U. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2012)
According to Skiba (2006), a learning space can be a formal space such as classrooms or a learning laboratory or as with the current generation, learning spaces are all locations where learning takes place. In order to stay in step in the evolution of learning spaces, library spaces should be able to adapt to the learning preferences of its users. This study is focused on knowing the current learning spaces of the UP students who are library users of the General Reference Section of the UP Main Library and its relation to the current library spaces of the General References section of the UP Main Library.
Seventy-two students who are users of the General Reference Section of the UP Diliman Main Library were surveyed. The survey questionnaire asked the respondents about the following profile of the respondents, locations of learning spaces, type of learning, factors and characteristics of learning spaces, evaluation of the General Reference Section's library spaces, spaces recommended for the General Reference Section and comments and suggestions about the General Reference Section.
The library and respondents' own residence are the most popular choices as their learning space and most of the respondents prefer either individual learning or a mix of individual and social learning rather than social learning alone as their type of learning. Noise level topped as the most important factor in a learning space and thermal comfort, general lighting and internet accessibility followed as important factors and characteristics for the respondents. The General Reference Section's conduciveness to learning, general lighting, security and safety, space for individual study, and noise level obtained very positive remarks from the respondents while the library's space for group discussion, thermal comfort and user's privacy obtained lowest ratings.
Overall, the students are satisfied with the current state and services offered by the General Reference Section of the UP Main Library. Most of the given factors and characteristics of learning space that are applicable to the General Reference Section obtained favorable ratings. Among the five most important factors and characteristics of a learning space according to the students, noise level, general lighting, Internet access and space for individual study got high ratings. Thermal comfort, which the students remarked as the second most important factor, got the second lowest ratings. They suggested putting more fans or acquiring air-conditioning units to address this problem. The General Reference Section is already a good learning space and an environment highly conducive to learning but making improvement according to the needs of students will be beneficial both for the library users and the library.
A recommended floor plan for the General Reference Section was done based on the findings of the study.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) General Reference Section. Main Library; School facilities -- Philippines -- Quezon City; Study environment -- Philippines -- Quezon City